THE IMPACT OF WORKING CAPITAL MANAGEMENT POLICIES ON FIRMS’ PROFITABILITY AND VALUE IN JORDAN (World Economics and Finance Bulletin, 2022)
This study aimed to identify the impact of working capital management policies on profitability and value in industrial and services listed in ASE. The sample study consisted of (66) industrial and service companies listed in ASE through the period (2014-2020), the study followed the descriptive and analytical approach and the use of many statistical methods such as descriptive statistics and regression analysis
Keywords: Working Capital Management Policies; Profitability; Market Value; ASE